2006
DOI: 10.1128/aem.72.1.185-191.2006
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variability and Distribution of Mating Type Alleles in Field Populations of Leptosphaeria maculans from France

Abstract: Leptosphaeria maculans is the most ubiquitous fungal pathogen of Brassica crops and causes the devastating stem canker disease of oilseed rape worldwide. We used minisatellite markers to determine the genetic structure of L. maculans in four field populations from France. Isolates were collected at three different spatial scales (leaf, 2-m 2 field plot, and field) enabling the evaluation of spatial distribution of the mating type alleles and of genetic variability within and among field populations. Within eac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
40
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(47 citation statements)
references
References 36 publications
4
40
3
Order By: Relevance
“…Genetic differences between eastern and western Australian isolates have previously been found using microsatellites and minisatellites, which were attributed to the presence of arid desert between the coasts (Hayden, Cozijnsen, & Howlett, 2007). Minisatellite markers used to analyse four field populations in France found high levels of gene and genotypic diversity within populations and high gene flow between populations, consistent with randomly mating populations (Gout et al, 2006) Dilmaghani et al (2012) also used minisatellite markers to show that the L. maculans population in Western Canada comprises two genetically distinct populations. A further study implementing fourteen minisatellite markers also found clonal sub populations of this pathogen on B. oleracea in Mexico (Dilmaghani et al, 2013).…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Genetic differences between eastern and western Australian isolates have previously been found using microsatellites and minisatellites, which were attributed to the presence of arid desert between the coasts (Hayden, Cozijnsen, & Howlett, 2007). Minisatellite markers used to analyse four field populations in France found high levels of gene and genotypic diversity within populations and high gene flow between populations, consistent with randomly mating populations (Gout et al, 2006) Dilmaghani et al (2012) also used minisatellite markers to show that the L. maculans population in Western Canada comprises two genetically distinct populations. A further study implementing fourteen minisatellite markers also found clonal sub populations of this pathogen on B. oleracea in Mexico (Dilmaghani et al, 2013).…”
Section: Introductionmentioning
confidence: 92%
“…juncea, B. rapa and B. oleracea: canola, vegetable and mustard crops (West, Kharbanda, Barbetti, & Fitt, 2001). This ascomycete was first described in 1791 by Tode and 1849 by Desmaziéres (Gout, Eckert, Rouxel, & Balesdent, 2006). Severe epidemics of blackleg disease occurred in Australia during the 1970s, wiping out the nascent canola industry .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…tritici was responsible for several resistance genes becoming ineffective for the control of yellow rust in four northwest European countries. Similarly, long-distance dispersal has been proposed to be responsible for the rapid breakdown of Rlm resistance genes in oilseed Brassica crops by Leptosphaeria maculans, the causal agent of stem canker of crucifers (Gout et al 2006). It should then be theoretically possible to reduce the risk of emergence of a new virulent (or resistant) pathogen by designing management strategies that limits gene/genotype flows among pathogen populations.…”
Section: Landscape Characteristics and Evolutionary Dynamics Of Pathogenmentioning
confidence: 99%
“…Genetic differences between eastern and western Australian isolates have previously been found using microsatellites and minisatellites, which were attributed to the presence of arid desert between the coasts (Hayden et al, 2007). Minisatellite markers used to analyse four field populations in France found high levels of gene and genotypic diversity within populations and high gene flow between populations, consistent with randomly mating populations (Gout et al, 2006a). Dilmaghani et al…”
Section: Introductionmentioning
confidence: 77%